Differences in the Academic Attributes of Matched and Unmatched Orthopaedic Surgery Residency Applicants are Narrowing. Issue 2 (13th April 2023) - Sudah, Suleiman Y.; Imam, Nareena; Sirch, Francis; Nicholson, Allen D.; Namdari, Surena; Menendez, Mariano E.
Abstract : Background: Orthopaedic surgery remains one of the most competitive residency specialties, with the number of applicants outpacing the availability of residency positions each year. The purpose of this study was to analyze present-day orthopaedic surgery match data, identify differences between matched and unmatched applicants, and compare our findings to previous trends. Methods: Applicant data from the National Resident Matching Program from 2016 to 2022 were analyzed. The number of matched and unmatched US allopathic senior orthopaedic applicants relative to the number of available positions was used to determine respective match rates. Performance metrics and applicant characteristics were compared by match status. Trends were compared with those of previous analysis from 2006 to 2014. Results: The number of applicants increased from 863 in 2016 to 1, 068 in 2022. The match rate decreased from 75% in 2016 to 66% in 2022 (p < 0.0001). Matched applicants had a higher number of contiguous ranks (12.3 vs. 6.5; p < 0.001), United States Medical Licensing Examination (USMLE) Step-1 score (248 vs. 240; p < 0.001), USMLE Step-2 score (255 vs. 247; p < 0.001), Alpha Omega Alpha (AOA) membership (38% vs. 13%; p < 0.001), and enrollment at a top 40 National Institutes of Health (NIH)-funded medical school (34% vs. 24%, p < 0.001). Compared with 2006 to 2014 data, a smaller percentage of matched applicants were enrolled in a top 40 NIH-funded medical school (34% vs. 37%, p = 0.013). The mean differences in USMLE Step-1 score (16 vs. 8.25 points, p < 0.001) and USMLE Step-2 score (16 vs. 8.25 points, p = 0.002) in favor of matched applicants nearly halved compared with that in 2006 to 2014. In addition, there was no longer a significant difference in the number of research products (abstracts, presentations, posters, and publications) between matched and unmatched applicants (p = 0.309). Conclusions: Differences in the academic attributes of matched and unmatched orthopaedic surgery applicants have become less profound over time, making it increasingly difficult to predict a successful match based on USMLE Step scores, AOA membership, research productivity, and medical school research reputation. Future studies should evaluate differences in subjective metrics (e.g., away rotation and interview performance and letters of recommendation) by match status.